Country Partnership Framework for the Republic of Turkey for the Period FY18-FY21 - World Bank (World Bank, Washington, DC, 2017)
This Country Partnership Framework (CPF) for Turkey covers the period FY18-21. It is aligned with the objectives of Turkey’s 10th Development Plan and is based on the findings of a World Bank Group (WBG) Systematic Country Diagnostic (SCD) that was finalized in February 2017. The CPF aims to help Turkey to achieve its development objectives through building on the foundations of the existing program and consolidating gains in key areas where the WBG is already active, as well as developing the program further in areas which target the WBG twin goals of reducing extreme poverty and boosting shared prosperity. The CPF puts forward a flexible approach for the WBG’s program that is appropriate for a middle-income country of Turkey’s size and takes account of the evolving country and regional situation.